A novel two-switch three-level active rectifier for grid-connected electrical appliances in smart grids - Monteiro, Vítor Duarte Fernandes (2018)
A novel topology of two-switch three-level active rectifier (TSTL-AR) is proposed in order to connect electrical appliances to smart grids considering power quality aspects. The proposed active rectifier is presented as a powerful solution to mitigate the negative effects of current harmonic distortion of the diode-bridge rectifiers, besides the ability of operating with unitary power factor. These aspects are particularly relevant considering the new paradigm of smart grids, where almost all the electrical appliances should be controlled in order to comply normative impositions of power quality. In addition, active rectifiers are also fundamental devices regarding the electric vehicle battery chargers, which are a new and significant class of electrical appliances for smart grids. In this paper, a comprehensive and detailed description of the novel topology of TSTL-AR is presented and compared with the classical power factor correction topology. Along the paper, it is discussed in detailed a digital current control structure based on finite control set model predictive control, permitting an accurate, robust, and faster control of the grid current. A laboratory prototype was developed and experimental tests were performed, verifying the precise operation, and demonstrating the importance of the proposed active rectifier for electrical appliances in smart grids. The results show a low level of current THD, a unitary power factor, and a regulated dc-link voltage.